On the importance of philosophy of law for lawyers: A case study from our judicial practice - Dajović Goran (Glasnik Advokatske komore Vojvodine, 2025)
This article attempts to shed light on the potential benefits that certain achievements and methods of the philosophy of law may have for legal practice. In this sense, the article first briefly presents the features of the philosophy of law as a discipline that studies law as such, followed by three of its perspectives that may also be of importance for lawyers. Subsequently, in light of these perspectives, a recent case from the practice of domestic misdemeanor courts is analyzed in detail. After the conducted analysis, it is concluded that the general deficiencies within the judicial and legal system of Serbia neither encourage nor favor the influence of the philosophy of law within legal practice. Nevertheless, this does not mean that they should not occupy a significant place within that practice. On the contrary, it seems that they can significantly contribute to its fundamental reform and the elimination of its most serious flaws.